Development of Biofuels Research in South Africa - Jimenez-Islas, Donaji; Perez-Romero, Miriam Edith; Cruz, Ignacio Ventura; Flores-Romero, Martha Beatriz (International Journal of Energy Economics and Policy, 2021)
The global biofuels have attracted a lot of attention because of their potential as a clean and renewable source of energy. The bibliometric method has been used for providing quantitative assessment of the field of biofuels research in South Africa. Data used in this study were obtained from Scopus database. The research covers such topics as the publications and citations, the document type, journals, leading authors, institutions, subjects, areas and keywords. The publications and citations data fitted the Gompertz model to find out the growth rate. Two stages in the evolution of publications and citations were found and coincide with the exponential behaviour. Biofuels research was identified to have an exponential growth from 2011 with a growth rate of 0.2628 years-1 (R2=0.93). This study demonstrates that the most documents were published in high-impact journals. Researchers would benefit from the findings because they would be able to see a trend in biofuels research in South Africa. Keywords: Bioethanol, biogas, biofuel, biodiesel JEL Classifications: Q16, Q20, Q42 DOI: https://doi.org/10.32479/ijeep.11454